Model intercomparison of the transport of aircraft-like emissions from sub- and supersonic aircraft - Helen Rogers; Hubert Teyssedre; Gianni Pitari; Volker Grewe; Peter van Velthoven; Jostein Sundet (Meteorologische Zeitschrift, 2002)
The IPCC Special Report on Aviation and the Global Atmosphere (PENNER et al., 1999) highlighted the variability between model calculations of both the impact of sub- and supersonic aircraft. This study provides valuable information on the transport of aircraft-like emissions from sub- and supersonic cruise altitudes and latitudes. The accurate reproduction of the transport of aircraft emissions from their source region is extremely important in any study of the atmosphere. The results of this tracer study have revealed that the transport of aircraft-like tracers is highly variable between models during a single two year integration. If aircraft emissions are considered to remain inactive in the atmosphere then model calculations predict that it is possible, within the course of only two years, to transport subsonic aircraft emissions from the midlatitude upper troposphere into the polar lower and middle stratosphere. This result emphasises the importance of reproducing the correct transport processes throughout the lower atmosphere in calculations of the atmospheric impact of aircraft. Der ,,IPCC Special Report on Aviation and the Global Atmosphere (PENNER et al., 1999)'' betonte die große Streuung der Modellergebnisse bezüglich des Einflusses von Unter- und Überschallluftverkehr. Die vorliegende Studie bietet nützliche Informationen zum Transport von Spurenstoffen, die Emissionsmuster aufweisen, welche vergleichbar sind mit Emissionen aus dem Unter- und Überschallreiseflug. Die genaue Wiedergabe des Transportes von Spurenstoffen des Luftverkehrs ist von besonderer Bedeutung für jede Untersuchung bezüglich des Luftverkehrseinflusses. Die Ergebnisse dieser Studie zeigen, dass der Transport von luftverkehrsähnlichen Spurenstoffen eine große Streuung unter den Modellen aufweist, bezogen auf eine zweijährige Simulation Unter der Annahme, dass Luftverkehrsemissionen passiv in der Atmosphäre transportiert werden, zeigen Modellrechungen, dass Spurenstoffe, die in mittleren Breiten in der oberen Troposphäre emittiert werden, innerhalb von zwei Jahren in die polare untere und mittlere Stratosphäre transportiert werden können. Die Ergebnisse zeigen deutlich die Notwendigkeit einer korrekten Modellierung von Transportprozessen der unteren Atmosphäre für die Untersuchung des Einflusses des Unter- und Überschallflugverkehrs auf die Atmosphäre.